1999
DOI: 10.1002/(sici)1521-4095(199912)11:18<1505::aid-adma1505>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Derivatized Mesoporous Silicon with Dramatically Improved Stability in Simulated Human Blood Plasma

Abstract: The stability of derivatized mesoporous silicon in a physiological environment is investigated and potential applications are discussed. It is shown that, while the surface of hydride‐terminated mesoporous silicon corrodes very rapidly upon exposure to simulated body fluid (see Figure), the dodecenyl‐terminated material is virtually untouched even after a much longer period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(59 citation statements)
references
References 9 publications
(14 reference statements)
0
56
0
3
Order By: Relevance
“…18 Any oxide present will then cause the PSi to degrade in aqueous solution. 14,19,20 With regard to stabilising PSi for drug delivery, Canham and co-workers 21 showed that using the hydrosilylation of dodecene to modify PSi the material showed little degradation over four weeks. Note however, that as dodecene renders the material hydrophobic, part of the reason for the excellent stability enhancement is that little or no water penetrates into the pore space.…”
Section: (L)mentioning
confidence: 99%
“…18 Any oxide present will then cause the PSi to degrade in aqueous solution. 14,19,20 With regard to stabilising PSi for drug delivery, Canham and co-workers 21 showed that using the hydrosilylation of dodecene to modify PSi the material showed little degradation over four weeks. Note however, that as dodecene renders the material hydrophobic, part of the reason for the excellent stability enhancement is that little or no water penetrates into the pore space.…”
Section: (L)mentioning
confidence: 99%
“…Functionalized porous silicon films were also placed into body fluids and their corrosion was showed to be reduced by two orders of magnitude compared to hydride-terminated samples. 8 Variations on this route include thermal instead of chemical catalysis of the hydrosilylation reaction. The reaction of an hydrogen-terminated porous silicon surface with desoxygeneted undecylenic acid at 95 C for 16 H under argon results in the formation of a (CH 2 ) 10 chain attached to the silicon surface via an Si-C bond on one end, and terminated with a carboxylic acid on the other end.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant being the ease of controlled manufacture of pSi with different porosities, pore sizes and structures to meet a specific application[l2, 16,20]. This is achieved by varying the dopant type and amount, current, charge densities and the etching solutions components and concentrations.…”
Section: Introductionmentioning
confidence: 99%